2017
DOI: 10.3390/s17112488
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network to Predict Vine Water Status Spatial Variability Using Multispectral Information Obtained from an Unmanned Aerial Vehicle (UAV)

Abstract: Water stress, which affects yield and wine quality, is often evaluated using the midday stem water potential (Ψstem). However, this measurement is acquired on a per plant basis and does not account for the assessment of vine water status spatial variability. The use of multispectral cameras mounted on unmanned aerial vehicle (UAV) is capable to capture the variability of vine water stress in a whole field scenario. It has been reported that conventional multispectral indices (CMI) that use information between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 93 publications
2
73
0
1
Order By: Relevance
“…In the context of precision agriculture, the application of UAS, their future prospects, and knowledge gaps are discussed in [53,[78][79][80][81]. While many horticultural crops have been studied using UAS technology, the most studied horticultural crops are vineyards [31,[82][83][84], citrus [85,86], peach [32,33], olive [18,87,88], pistachio [89,90], and almond [91][92][93][94], among others [95][96][97][98][99]. Some of the UAS types used for water status studies of horticultural crops are shown in Figure 2.…”
Section: Unmanned Aircraft Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of precision agriculture, the application of UAS, their future prospects, and knowledge gaps are discussed in [53,[78][79][80][81]. While many horticultural crops have been studied using UAS technology, the most studied horticultural crops are vineyards [31,[82][83][84], citrus [85,86], peach [32,33], olive [18,87,88], pistachio [89,90], and almond [91][92][93][94], among others [95][96][97][98][99]. Some of the UAS types used for water status studies of horticultural crops are shown in Figure 2.…”
Section: Unmanned Aircraft Systemsmentioning
confidence: 99%
“…Thus, such stress is reflected in the vegetation profile and easily captured by indices, such as NDVI. For this reason, NDVI has shown correlations with a wide array of crops response including vigour, chlorophyll content, leaf area index (LAI), crop water stress, and occasionally yield [34,[82][83][84]127]. The rededge band covers the portion of the electromagnetic spectrum between the red and NIR bands where reflectance increases drastically.…”
Section: Hyperspectralmentioning
confidence: 99%
See 3 more Smart Citations